Odpowiedzi

2010-01-31T15:09:32+01:00
A)[(x-5)(x+3)+(2x+4)(x+1)](x+3)
[(x kwadrat -3x-5x-15)+(2x kwadrat + 2x+4x+4)] *(x+3)
x kwadrat- 8x-15+2x kwadrat+6x +4 +x+3
3 x kwadrat- 13x -8
b)(2-x)[(x+2)(x-4)-(2x+1)(-x-3)]
2-x [x kwadrat - 4x+2x-8-2x kwadrat-6x-x-3
2-x * x kwadrat- 4x+2x-8-2x kwadrat-6x-x-3
-9-9x-x kwadrat
c)(x-3)[(3x+1)(2x-2)+(4-2x)(5x-1)]
x-3+[6x kwadrat-6x+2x-2+20x-4-10x kwadrat + 2x]
19x-7x-4x kwadrat
d)[(x+1)(3x-4)-(x+5)(2x-1)](x+1)
[3x kwadrat - 4x +3x-4-2x kwadrat-x+10x-5+x+1
x kwadrat - 3x-8
2010-01-31T15:31:08+01:00
A) [(x-5)(x+3)+(2x+4)(x+1)](x+3)=[x²+3x-5x-15+2x²+2x+4x+4](x+3)=[3x²+4x-11](x+3)=3x³+9x²+4x²+12x-11x-33=3x³+12x²+x-33

b) (2-x)[(x+2)(x-4)-(2x+1)(-x-3)]=(2-x)[(x²-4x+2x-8)-(-2x²-6-x-3)]=(2-x)(x²-4x+2x-8+2x²+6+x+3)=(2-x)(3x²-x-1)=6x²-2x-2-3x³-x²+x=7x²-3x³-x-2

c) (x-3)[(3x+1)(2x-2)+(4-2x)(5x-1)]=(x-3)[6x²-6x+2x-2+20x-4-10x²+2x]=(x-3)[-4x²+18x-6]=-4x³+18x²-6x+12x²-54x+18=-4x³+30x²-60x+18

d) [(x+1)(3x-4)-(x+5)(2x-1)](x+1)=[(3x²-4x+3x-4)-(2x²-x+10x-5)](x+1)=(3x²-4x+3x-4-2x²+x_10x+5)(x+1)=(x²-10x+1)(x+1)=x³-10x²+x+x²-10x+1=x³-9x²-9x+1